Solid-state compounds of 2-methoxybenzylidenepyruvate with some bivalent metal ions - Synthesis, characterization and thermal behavior studies - Kobelnik, M. [UNESP]; Schnitzler, E.; Ionashiro, Massao [UNESP] (Springer, 2008)
Solid-state M-2-MeO-BP compounds, where M represents bivalent Mn, Fe, Co, Ni, Cu, Zn and 2-MeO-BP is 2-methoxybenzylidenepyruvate have been synthesized. Simultaneous thermogravinietry-differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, elemental analysis and complexometry were used to characterize and to study the thermal stability and thermal decomposition of these compounds. The results led to information about the composition, dehydration, crystallinity and thermal decomposition of the isolated compounds.
Keywords: 2-methoxybenzylidenepyruvate; Bivalent transition metals; Characterization; Thermal behavior; Backpropagation; Chemical analysis; Chemical modification; Cobalt compounds; Decomposition; Differential scanning calorimetry; Gravimetric analysis; Infrared spectroscopy; Iron; Manganese; Manganese compounds; Metal analysis; Metal ions; Mixtures; Nickel; Photoresists; Pyrolysis; Scanning; Spectroscopic analysis; Spectroscopy; Spectrum analysis; Tellurium compounds; Thermoanalysis; Thermogravimetric analysis; X ray analysis; X ray spectroscopy; Zinc; 2 methoxybenzylidenepyruvate; Bivalent metal ions; Business media; Complexometry; crystallinity; Differential scanning calorimetry (photo-DSC); Elemental analysis (EA); Infrared (IR); Isolated compounds; Solid-state compounds; Springer (CO); thermal stability; x-ray powder diffractometry; Differential thermal analysis